PENGARUH SAUDI VISION 2030 DAN AGENDA FOREIGN DIRECT INVESTMENT(FDI) ARAB SAUDI DI INDONESIA - Sianturi, Nevlita; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Saudi Arabia is a rich country whose source of income is almost 90% comes from oil and gas. However, since December 2014 world oil prices plummeted to US $ 40 per barrel, previously had felt the world oil price above US $ 100 per barrel. In addition to the phenomenon of the world oil price drop caused by rising production of US Shale oil, the constellation of politics in the Middle East continues to heat up also trigger Saudi Arabia to reform its economy for Saudi Arabia off its dependence with oil by diversifying its economy and become a middle power country in the Middle East region And Arab countries. The Saudi Arabian Reform effort is contained in Saudi Vision 2030.Indonesia is one of Saudi Arabia's vital partners in realizing Saudi Vision 2030. The Saudi Arabian focus on economics in Saudi Vision 2030 is the Foreign Direct Investment Agenda (FDI). In analyzing the influence of Saudi Vision 2030 on the Saudi Foreign Direct Investment Agenda in Indonesia, this research uses a perspective of liberalism supported by the concept of the nation state and FDI theory. Saudi Vision 2030 has a positive influence on the increase of Saudi Arabian cooperation in the field of economy especially in the field of Investment, as seen from the visit of King Salman to Indonesia, the signing of 11 MoUs, Realization of Saudi Arabia Investment in the first quarter of 2017 showed a positive increase and optimistic will continue to rise Which is significant and also the investment policy that is constantly updated by both countries to facilitate each other and give comfort to invest.Keywords: Saudi Arabia, Economic Reform, Foreign Direct Investment (FDI), Economic Diversification, Saudi Vision 2030